Integrating technology in physical education: The impact of TPACK-based tactical and technical approaches on football skills and student motivation - Mulyana, Defri; Suherman, Adang; Komarudin, Komarudin; Abduljabar, Bambang; Mulyana, Fegie Rizkia (Physical Education and Sports: Studies and Research, 2025)
Background: Motivation and skill development are vital in physical education, particularly football. Tactical learning emphasizes decision-making and game understanding, while technical learning focuses on mastering fundamental skills. Objectives: This study aimed to analyze the impact of a TPACK-based tactical and technical learning approach on student motivation and football skill acquisition among high school students in Tasikmalaya. Methods: The study applied the TPACK framework—integrating Technological, Pedagogical, and Content Knowledge—in designing the learning model. Using an experimental method with a pre-test–post-test design, 30 students were divided into two groups. Motivation was assessed via a Likert-scale questionnaire, while football skills (passing, heading, dribbling, shooting, and playing ability) were evaluated through standardized tests. Data were analyzed using paired and independent t-tests with a significance level of p < 0.05. Results: The technical approach significantly enhanced basic football skills, notably heading (t = 8.47) and shooting (t = 8.29), proving its effectiveness in improving fundamental competencies. Conversely, the tactical approach showed a notable increase in student motivation (t = 4.98) and playing ability (t = 5.94), reflecting its strength in fostering strategic understanding and engagement. TPACK integration further reinforced both approaches through effective use of technology. Conclusions: The study highlights the importance of combining tactical and technical approaches to promote holistic student development. Continued research is needed to explore the long-term effects and potential of integrating diverse technological tools in physical education.